2013
DOI: 10.1002/masy.201300014
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Multi‐Angle Light Scattering in Polyolefin Characterization

Abstract: Summary: The paper reviews basic principles and applications of multi-angle light scattering (MALS) employed as a detector for high temperature size exclusion chromatography (SEC). The presented MALS data were acquired with state-of-the-art MALS instrumentation. A special attention is paid to the specific elution behavior of branched polyolefins during their SEC separation, to the characterization of long chain branching, and to overcoming the limitations arising from abnormal SEC elution. The MALS detection i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…[13,29,46] The GPC method has a higher sensitivity to the low levels of LCB in randomly long-chain branched PEs having high MWs. [61] Yu et al [43] found a detection limit of 0.01 LCB/1000 carbons (<1 × 10 −5 ) for MWs equal to or greater than 200 000 g mol −1 , and 0.005 LCB/1000 carbons (5 × 10 −6 ) for MWs equal to or greater than 1 000 000 g mol −1 . At these LCBD levels, the background noises in GPC measurements are lower than the comparable NMRs.…”
Section: Detectormentioning
confidence: 99%
See 1 more Smart Citation
“…[13,29,46] The GPC method has a higher sensitivity to the low levels of LCB in randomly long-chain branched PEs having high MWs. [61] Yu et al [43] found a detection limit of 0.01 LCB/1000 carbons (<1 × 10 −5 ) for MWs equal to or greater than 200 000 g mol −1 , and 0.005 LCB/1000 carbons (5 × 10 −6 ) for MWs equal to or greater than 1 000 000 g mol −1 . At these LCBD levels, the background noises in GPC measurements are lower than the comparable NMRs.…”
Section: Detectormentioning
confidence: 99%
“…The short-term reproducibility and long-term stability of the triple-detection GPC are also excellent. [43,61] In addition, this method can be applied to the studies on star polymers, e.g., to elucidate the chain conformation of the star PEs. [62,63] Despite those advantages mentioned above, the tripledetection GPC method has several limitations in the LCB measurement: the first is that the measurement noise has a serious effect on the accuracy in determining the LCBD, which is possibly a main limitation of the triple detection SEC.…”
Section: Detectormentioning
confidence: 99%
“…Other common applications include establishing the degree of post-translational modification and polydispersity of glycoprotein, lipoproteins and similar conjugates 4,31,44,45,46,47 ; the formation (or lack thereof) and absolute stoichiometry (as opposed to stoichiometric ratio) of heterocomplexes including protein-protein, protein-nucleic acid and protein-polysaccharide complexes 24,46,48,49,50,51,52 ; determining the monomer-dimer equilibrium dissociation constant 49,53,54 ; and evaluating protein conformation 55,56 . Beyond proteins, SEC-MALS is invaluable for characterization of peptides 57,58 , broadly heterogeneous natural polymers such as heparins 59 and chitosans 60,61 , small viruses 62 and most types of synthetic or processed polymers 63,64,65,66 . An extensive bibliography may be found in the literature 67 and online (at http:// www.wyatt.com/bibliography).…”
Section: Introductionmentioning
confidence: 99%
“…Considering that g reflects predominantly the high molecular tail of the MWD, i.e. the most branched fraction [42], this would mean a higher amount of molecules with a wider variety in their LCB content with increasing degradation time.…”
Section: Contraction Factorsmentioning
confidence: 99%
“…The mean square radius of gyration is related with the molar mass for linear polyethylene by Ref. [42] …”
Section: Contraction Factorsmentioning
confidence: 99%